An immunohistochemical analysis of Rab27B distribution in fetal and adult tissue - Hendrix, An (2017)
Regulated secretory pathways coordinated by small Rab GTPases are critically involved in intercellular communications. Here, we report the expression and localization of Rab27B in developing and differentiated epithelial human tissues by immunohistochemistry. Rab27B is poorly expressed in fetal tissues suggesting that several developmental mechanisms involved in epithelial differentiation and functions are mediated by other secretory Rab GTPases, such as Rab27A or Rab3 family members. In adult tissues, Rab27B is expressed in a wide variety of differentiated secretory epithelial cells, including those lining the salivary gland, gastrointestinal, mammary and prostate tracts. The complex pattern of Rab27B expression indicates that dysregulation of Rab27B-mediated secretion may have profound implications for disease pathology.